Effects of Subchronic Exposure to N, N-Diethyl-m-toluamide on Selected Biomarkers in Common Carp (Cyprinus carpio L.). (30th March 2014) - Slaninova, Andrea; Modra, Helena; Hostovsky, Martin; Sisperova, Eliska; Blahova, Jana; Matejova, Iveta; Vicenova, Monika; Faldyna, Martin; Zelnickova, Lenka; Tichy, Frantisek; Svobodova, Zdenka
Abstract : DEET ( N, N -diethyl- m -toluamide) is the most common active ingredient in the insect repellents commonly detected in European groundwater. The aim of this study was to investigate the effect of subchronic DEET exposure on biochemical and haematological parameters, antioxidant enzymes, including catalase, glutathione peroxidase, glutathione reductase, and glutathione S-transferase, and the amount of thiobarbituric acid reactive substances (TBARS) in common carp ( Cyprinus carpio L.). Two specific proinflammatory and anti-inflammatory cytokine genes were selected to assess an immunological status of the fish. Fish were exposed for 28 days to three concentrations of DEET (1.0 µg/L, 0.1 mg/L, and 1.0 mg/L) where 1 µg/L is corresponding to the concentration found in the environment. DEET had a significant ( P < 0.05 ) effect on increased RBC, decreased mean corpuscular volume (MCV), and mean corpuscular haemoglobin value (MCH) compared to control groups in the concentration of 1 mg/L. A significant decline ( P < 0.05 ) in triacylglycerols (TAG) in plasma was found in the concentration of 1 mg/L compared to the control groups. The parameters of oxidative stress in tissues of common carp were weekly affected and immunological parameters were not affected.